Pengaruh Lingkungan Kerja, Komunikasi, dan Gaya Kepemimpinan Terhadap Partisipasi Aktif Studi Pada Anggota Organisasi Pemuda Melikan Lor (OPEL) Kelurahan Bantul, Kapanewon Bantul, Kabupaten Bantul - Ade Nugraha, Rui Restu; Prasetya, Bangun Putra (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of work environment, communication, and leadership style on the active participation of members of the Melikan Lor Youth Organization (OPEL) in Bantul Village, Kapanewon Bantul, Bantul Regency. This research uses a quantitative approach with a population of all OPEL members totaling 163 people. The research sample was active members of OPEL, with non-probability sampling technique and simple random sampling method, the results of Slovin's calculation resulted in 116 respondents. Primary data was collected through a questionnaire using a Likert scale. The results of research show that the work environment and leadership style partially have a positive and significant effect on the active participation of OPEL members. However, communication partially has no significant influence on active participation. Simultaneously (together), work environment, communication, and leadership style have a significant effect on the active participation of OPEL members. The coefficient of determination (R²) shows that 45.4% of the variation in active participation is explained by the three independent variables, while the rest is influenced by other variables outside the study.